HERPETOFAUNA DIVERSITY IN MID-SUCCESSIONAL FORESTS OF MT. BANAHAW DE LUCBAN, PHILIPPINES: Herpetofauna in Mid-successional forests of Mt. Banahaw de Lucban - Ronald C. Garcia; Amalia E. Almazol; Dennis E. Pulan; Almar John A. Luna; Liam Karl C. Manago; Francisco N. Beltran; Eraldwin A. Dimailig; Daniel S. Galeon; John Louis S. Narinay; Gracelle L. Ann Zoleta; Judy Ann Develuz (SEAMEO BIOTROP, 2026)
ARTICLE HIGHLIGHTS- Active forest restoration via reforestation hastens forest cover re-establishment and recovers ecosystem health.- Due to the sensitivity of herpetofauna to environmental changes, they are a good indicator of ecosystem health.- This study compares herpetofauna diversity in reforestation areas and natural secondary growth mid-successional forests to determine the impacts of active forest restoration and conservation initiatives in promoting ecosystem recovery and health. - The results can assist decision makers in formulating sustainable forest and ecosystem health restoration strategies.ABSTRACTHerpetofauna are sensitive to environmental changes, making them good indicators of ecosystem health. This study assessed the diversity of herpetofauna species in the mid-successional forest consisting of 30-year reforestation areas and natural secondary-growth forests of Mount Banahaw de Lucban (MBdL) to determine the impacts of forest restoration and conservation initiatives in promoting ecosystem recovery and health. A combination of belt transects following forest trails and purposive sampling was employed where samples were captured via net or hand-picked. Results revealed 26 herpetofauna species composed of 11 amphibians and 15 reptiles, including snakes and lizards. These findings are significantly higher than previously reported. Herpetofauna had moderate diversity at 2.219 and 1.903 in the Shannon Diversity Index (H’) for amphibians and reptiles, respectively. Species richness (Ra) was 7.091 for amphibians and 3.533 for reptiles, with dominance (D) values of 0.110 and 0.260 and evenness (J’) values of 0.925 and 0.703, respectively. Using the Chi-square test for Independence, however, these differences between reforestation and secondary forest were found significant (X2 = 12.64, P = 0.002, d = 2) for species abundance but not for species richness. Platymantis banahao, P. luzonensis, Gonocephalus semperi, Boiga angulata, Ptyas luzonensis, and Malayopython reticulatus were threatened species. Results imply that the reforestation, forest protection, and conservation efforts for more than 30 years have increased forest cover, and improved ecosystem health favoring herpetofauna species.